PHONOLOGICAL PROCESSES AND ADAPTION CROSS LINGUISTIC EXAMINATION: A SYSTEMATIC LITERATURE REVIEW - Melani S, Rhosa (Universitas Negeri Surabaya, 2026)
The primary objective of this study is to examine phonological processes and adaptations across various languages, focusing on their influence on language acquisition, literacy development, and second language learning. The research spans from 2019 to 2024, covering recent studies in the field. Databases such as Google Scholar and Crossref were used for the initial search, utilizing tools like Zotero and Publish or Perish. Keywords such as